If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2x = 10 Reorder the terms: 2x + 4y = 10 Solving 2x + 4y = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 2x + 4y + -4y = 10 + -4y Combine like terms: 4y + -4y = 0 2x + 0 = 10 + -4y 2x = 10 + -4y Divide each side by '2'. x = 5 + -2y Simplifying x = 5 + -2y
| 2x+3x^2+4y=32x | | -[m-(-4)]-(-m-5)-2(3m-7)=-(-7-2m) | | 22-13=3(x-3) | | 12n-n=-2+13 | | 0.25m+0.m=9.8 | | 3(4y+2)-22=4(5y-5)-14 | | -1225-12x=-1705 | | x+25+3x=-14-3x-17 | | (x+[x+6])*2=60 | | -7a-1=13 | | 12-4=3n-11n | | -1225-12x=0 | | -15+2x=21-x+4x | | 2x+x=160 | | 6(3x-2)=5(2x-2) | | x+(x+6)*2=60 | | -3(5k+8)=-24 | | -13=-h-(7) | | 17x+x+3x= | | 3(X+2)-(2X-7)=-(5X-1)-2(X+6) | | 6x=2y | | x(x+6)*2=60 | | 2y=-30 | | 10-3b=1-6b | | 5x-[2+3(1-x)]=2x+2(x-1) | | 5u^2+(-9u)+2=0 | | 7x^2+6x+4=0 | | 2(n+6)=-n | | .45+18n=441 | | 9h-3h=15 | | 2(3x+6)+4(4x+5)+3=22x+36 | | 4x^2+120=120 |